Structural Topology Design for Electromagnetic Performance Enhancement of Permanent-Magnet Machines - Pengjie Xiang; Liang Yan; Xiaoshuai Liu; Xinghua He; Nannan Du; Han Wang (Chinese Journal of Mechanical Engineering, 2025)
Abstract Permanent-magnet (PM) machines are the important driving components of various mechanical equipment and industrial applications, such as robot joints, aerospace equipment, electric vehicles, actuators, wind generators and electric traction systems. The PM machines are usually expected to have high torque/power density, low torque ripple, reduced rotor mass, a large constant power speed range or strong anti-magnetization capability to match different requirements of industrial applications. The structural topology of the electric machines, including stator/rotor arrangements and magnet patterns of rotor, is one major concern to improve their electromagnetic performance. However, systematic reviews of structural topology are seldom found in literature. Therefore, the objective of this paper is to summarize the stator/rotor arrangements and magnet patterns of the permanent-magnet brushless machines, in depth. Specifically, the stator/rotor arrangements of the PM machines including radial-flux, axial-flux and emerging hybrid axial-radial flux configurations are presented, and pros and cons of these topologies are discussed regarding their electromagnetic performance. The magnet patterns including various surface-mounted and interior magnet patterns, such as parallel magnetization pole pattern, Halbach arrays, spoke-type designs and their variants are summarized, and the characteristics of those magnet patterns in terms of flux-focusing effect, magnetic self-shielding effect, torque ripple, reluctance torque, magnet utilization ratio, and anti-demagnetization capability are compared. This paper can provide guidance and suggestion for the structure selection and design of PM brushless machines for high-performance industrial applications.